Karakteristik Keinovatifan Dan Persepsi Petani Padi Sawah Terhadap Saluran Komunikasi Dalam Pengelolaan Usahatani Padi Sawah Di Kecamatan Seram Utara Timur Kobi Kabupaten Maluku Tengah - Risyart Alberth Far-Far (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2026)
The development of rice as a staple food in Indonesia continues to be enhanced to address the global food crisis and climate change, particularly in rice production centers. The objective of this study was to describe the innovative characteristics of rice farmers and to understand their perceptions of extension communication channels regarding information on rice farming management in the North Seram Timur Seti District, Central Maluku Regency. This study employed a quantitative method with a descriptive approach. The research method used was a survey. A questionnaire was used as the data collection instrument. The study location was in the North Seram Timur Seti District, Central Maluku Regency. Data analysis was presented descriptively. Descriptive analysis was conducted by creating a table of average scores from the primary data. The results showed that rice farmers in the North Seram Timur District, Central Maluku Regency exhibited good innovative characteristics in socioeconomic, individual, and communication aspects. Farmers' perceptions of interpersonal and media communication channels were good in terms of availability and ease of access, appropriateness of interpersonal communication channel use, and appropriateness of media communication channel use. Thus, in general, rice farmers in North East Seram District, Central Maluku Regency have high innovative characteristics and positive perceptions of interpersonal and media communication channels.